Arthroscopically Assisted Percutaneous Screw Fixation of Tibial Plateau Fractures. Issue 2 (1st April 2022) - Jabara, Justin T.; Only, Arthur J.; Paull, T. Zach; Wise, Kelsey L.; Swiontkowski, Marc F.; Nguyen, Mai P.
Abstract : Background: Tibial plateau fractures account for approximately 1% to 2% of fractures in adults 1 . These fractures exhibit a bimodal distribution as high-energy fractures in young patients and low-energy fragility fractures in elderly patients. The goal of operative treatment is restoration of joint stability, limb alignment, and articular surface congruity while minimizing complications such as stiffness, infection, and posttraumatic osteoarthritis. Open reduction and internal fixation with direct visualization of the articular reduction or indirect evaluation with fluoroscopy has traditionally been the standard treatment for displaced tibial plateau fractures. However, there has been concern regarding inadequate visualization of the articular surface with open tibial plateau fracture fixation, contributing to a fivefold increase in conversion to total knee arthroplasty 2 . In addition, the risk of wound complications and infection has been reported to be as high as 12% 3, 4 . Knee arthroscopy with percutaneous, cannulated screw fixation provides a less invasive procedure with excellent visualization of the articular surface and allows for accurate reduction and fracture fixation compared with traditional open reduction and internal fixation techniques 1 . Recent studies of arthroscopically assisted percutaneous screw fixation of tibial plateau fractures have reported excellent early clinical and radiographic outcomes and low complication rates 3, 5, 6 . Description: This technique involves the use of both arthroscopy and fluoroscopy to facilitate reduction and fixation of the tibial plateau fracture. Through a minimally invasive technique, the depressed articular joint surface is targeted with use of preoperative computed tomography (CT) scans and intraoperative biplanar fluoroscopy. Reduction is then directly visualized with arthroscopy and fixation is performed with use of fluoroscopy. Lastly, restoration of the articular surface is confirmed with use of arthroscopy after definitive fixation. Modifications can be made as needed. Alternatives: The traditional method for fixation of displaced tibial plateau fractures is open reduction and internal fixation. Articular reduction can be visualized directly with an open submeniscal arthrotomy and an ipsilateral femoral distractor or indirectly with fluoroscopy. Rationale: Visualization of the articular surface is essential to achieve anatomic reduction of the joint line. Inspection of the posterior plateau is difficult with an open surgical approach. Arthroscopically assisted percutaneous screw fixation of a tibial plateau fracture may allow for improved restoration of articular surfaces through enhanced visualization. Less soft-tissue dissection is associated with lower morbidity and may result in less damage to the blood supply, lower rates of infection and wound complications, faster healing, and better mobility for patients. In our experience, this technique has been successful in patients with severe osteoporosis and comminution of depressed fragments. If total knee arthroplasty is required, we have also observed less damage to the blood supply and fewer surgical scars with use of this surgical technique. Expected Outcomes: Arthroscopically assisted percutaneous screw fixation of a tibial plateau fracture facilitates anatomical reduction through a less invasive approach. Patients undergoing this method of tibial plateau fracture fixation are able to engage earlier in rehabilitation 2 . Studies have shown early postoperative range of motion, excellent patient-reported outcomes, and minimal complications 7, 8 . Important Tips: Arthroscopically assisted fixation can be applied to a variety of tibial plateau fractures; however, the minimally invasive approach is best suited for patients with isolated lateral tibial plateau fractures (Schatzker I to III) and a cortical envelope that can be easily restored. The cortical envelope refers to the outer rim of the tibial plateau. Fracture pattern and ligamentotaxis determine the cortical envelope, which can be evaluated on preoperative CT scans. In our experience, even depressed segments with a high degree of comminution may be treated with use of this technique with satisfactory results. Articular depression should be targeted with use of a preoperative CT scan and intraoperative fluoroscopy and arthroscopy. The surgeon should be careful not to "push up" in 1 small area; rather, a "joker" elevator or bone tamp should be utilized, moving anterior to posterior, which can be frequently assessed with arthroscopy. The intra-articular pressure of the arthroscopy irrigation fluid should be low (≤45 mm Hg or gravity flow), and the operative extremity should be monitored for compartment syndrome throughout the procedure. Acronyms and Abbreviations: ACL = anterior cruciate ligament K-wires = Kirschner wires ORIF = open reduction and internal fixation AP = anteroposterior CR = computed radiography